(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Scholarship has often overlooked how Native Americans, who are disproportionately imprisoned, have developed tactics to cope with long-term imprisonment. Drawing on the authors’ correspondences and conversations, this essay features decolonial performances for survival and prison abolition, which George Blue Bird (Oglala Lakota) has enacted within conditions of carceral violence. These interlocking tactics are 1. nurturing connections with more-than-humans; 2. “drifting,” Blue Bird’s term for imagining, traveling to, and inhabiting other realms; and 3. activating freedom and futurities. Ultimately, we focus on what these tactics and Lakota epistemologies offer the prison abolition movement.